Biochemical Analysis Of Some Dried Sis Fishes Of The River Padma In Rajshahi - Sultana, Sabina; Parween, Selina; Hossain, M Altaf (Journal of Life and Earth Science, 2012)
Seven different species viz. Chanda baculis, Chanda ranga, Amblypharyngodon mola, Oxygaster bacaila, Clupisoma atherinoides, Corica soborna, Mystus vittatus and a group of mixed SIS fishes viz. Mastacembelus pancalus, Xenntodon cancila, Chanda baculis and Glossogobius giuris were used for preparation of dust which can be preserved for a time period. The fishes were sun dried or oven dried, which are also method of preservation. Quality of the oven-dried fish was better than that of the sun-dried fish, but sun-drying process is easy and can be used in large scale. The fish powder remained in good condition for 7-9 months at normal room temperature, but at -18°C the powder was in good condition throughout the year. Highest quantity of powder from 1 kg of fish was obtained in case of the mixed species as 24.61% and the lowest in O. bacaila which was 20.52%. Biochemical analysis showed that the maximum calcium content was found as 1.34% in M. vittatus and minimum was 0.80% in mixed SIS fishes. Maximum phosphorus content was 2.90% in C. ranga and minimum was 1.72% in C. soborna. Maximum iron content was found as 45.20 mg/100g in mixed SIS fishes and minimum was found as 16.85 mg/100g in O. bacaila. The maximum moisture content was found in C. ranga (13.50%) and the minimum in mixed SIS fishes (11.65%). The maximum protein content was recorded in the mixed SIS fishes (72.45%) and the minimum in C. ranga (52.65%). The experiment was replicated three times and conducted from July 2005 to July 2008. DOI: http://dx.doi.org/10.3329/jles.v6i0.9719 JLES 2011 6: 39-43